Exploring mHealth Solutions: A Case Study on the Influence of mHealth Technologies on Communication and Information Sharing at Hamilton Health Sciences - Aceti, Victoria (University of Ottawa (Canada), 2010)
The recognition of the need to improve communication has led healthcare organizations to integrating health informatics technologies. This study investigated the extent to which mHealth applications influenced communication and information sharing patterns between interdisciplinary healthcare providers in the delivery of healthcare services. The study was conducted at a multi-campus health organization in Ontario. Sociotechnology theory examines the influence of sociological factors in the introduction and use of information and communication technologies. Through a sociotechnical approach, this research study focused on how the communicative and social aspects of an organization influence health informatics integration, as well as the extent to which information sharing and communication patterns were influenced. This study found that several factors contributed to the integration of mHealth technologies, including: significant end user contribution to system design, an organizational culture open to technological change, the use of creative internal communication practices, training, and evaluation procedures. Findings indicated that the limited use of mHealth technologies were a result of poor ergonomical design and a lack of employee consultation prior to integration. That being said, participants indicated that the accessibility of information and convenience of mHealth technologies ameliorated their work routines. Research shows that health informatics has the potential to improve healthcare service delivery, and consequently, future studies must look at the affect of these technologies on the fundamental elements of healthcare, including communication and information sharing patterns among healthcare providers.
Keywords: Information Technology.; Mass Communications.; Health Sciences, Health Care Management.